Understanding the nature of science and scientific progress: A theory-building approach - Maria Chuy; Marlene Scardamalia; Carl Bereiter; Fleur Prinsen; Monica Resendes; Richard Messina; Winifred Hunsburger; Chris Teplovs; Angela Chow (The Canadian Network for Innovation in Education (CNIE), 2010)
In 1993 Carey and Smith conjectured that the most promising way to boost students' understanding of the nature of science is a "theory-building approach to teaching about inquiry." The research reported here tested this conjecture by comparing results from two Grade 4 classrooms that differed in their emphasis on and technological support for creating and improving theories. One class followed a Knowledge Building approach and used Knowledge Forum®, which together emphasize theory improvement and sustained creative work with ideas. The other class followed an inquiry approach mediated through collaborative project-based activities. Apart from this, the two classes were demographically similar and both fell within the broad category of constructivist, inquiry-based approaches and employed a range of modes and media for investigative research and reports. An augmented version of Carey and Smith's Nature of Science Interview showed that the Knowledge Building approach resulted in deeper understanding of the nature of theoretical progress, the connections between theories and facts, and the role of ideas in scientific inquiry.